Feasibility Study on Biomonitoring of Microplastics in Fish Gastrointestinal Tracts - De Witte, Bavo; Catarino, Ana I.; Vandecasteele, Loes; Dekimpe, Michael; Meyers, Nelle; Deloof, Daphné; Pint, Steven; Hostens, Kris; Everaert, Gert; Torreele, Els (Frontiers in Marine Science, 2022)
Monitoring the occurrence and trends of microplastic contamination in the marine environment is key to establish microplastic (MP) data baselines, to work out policy mitigation measures, and to assess the effectiveness of waste regulations. To establish MP contamination baselines in the marine environment, marine biota species can be selected as monitoring matrices to track plastic pollution in the environment. The aim of this work was to evaluate the feasibility of biomonitoring MPs in fish gastrointestinal tract (GIT). A selection of suitable fish species was performed, based on species distribution, sampling effort, commercial value of species, sustainable development of fish populations, migration behaviour, and scientific evidence for occurrence of MPs in the fish GIT. Sampling and MP extraction protocols were developed and validated on fish GIT samples acquired in the Southern North Sea. The fish species selection protocol enabled the selection of ubiquitous distributed and non-endangered fish species relevant for MP monitoring in the North Sea. The fish GIT sampling protocol considered background contamination measures and sampling fillet as procedural blanks. Advantages and disadvantages of onboard dissection were discussed. The MPs extraction protocol was based on matrix digestion, density separation, and Nile red staining of particles followed by fluorescent microscopy observation. The confirmation of MPs identification and the analysis of the polymer composition was done using micro-Fourier transform infrared (μFTIR) spectroscopy. The MP analysis indicated a low number of MPs in the fish GIT. The mean number of particles per single fish GIT was 0.48 ± 0.81 (Nile red staining observations) to 0.26 ± 0.64 (corrected for background contamination). A power analysis (sampling effort) indicated that to detect significant differences, in a balanced-ANOVA type of analysis, between species and/or sampling areas, the sample size would require a minimum of 109 up to 370 individual fish. The feasibility of MP biomonitoring in fish GIT was assessed by a SWOT-analysis, which indicated that fish GIT is a suitable matrix for biomonitoring of MPs, but that the large number of samples needed to identify significant differences can be a major drawback. A potential implementation strategy for MP biomonitoring within Europe was suggested.